The novel rexinoid MSU-42011 is effective for the treatment of preclinical Kras-driven lung cancer - Jessica A. Moerland (Nature Portfolio, 2020)
Abstract Effective drugs are needed for lung cancer, as this disease remains the leading cause of cancer-related deaths. Rexinoids are promising drug candidates for cancer therapy because of their ability to modulate genes involved in inflammation, cell proliferation or differentiation, and apoptosis through activation of the retinoid X receptor (RXR). The only currently FDA-approved rexinoid, bexarotene, is ineffective as a single agent for treating epithelial cancers and induces hypertriglyceridemia. Here, we used a previously validated screening paradigm to evaluate 23 novel rexinoids for biomarkers related to efficacy and safety. These biomarkers include suppression of inducible nitric oxide synthase (iNOS) and induction of sterol regulatory element-binding protein (SREBP). Because of its potent iNOS suppression, low SREBP induction, and activation of RXR, MSU-42011 was selected as our lead compound. We next used MSU-42011 to treat established tumors in a clinically relevant Kras-driven mouse model of lung cancer. KRAS is one of the most common driver mutations in human lung cancer and correlates with aggressive disease progression and poor patient prognosis. Ultrasound imaging was used to detect and monitor tumor development and growth over time in the lungs of the A/J mice. MSU-42011 markedly decreased the tumor number, size, and histopathology of lung tumors compared to the control and bexarotene groups. Histological sections of lung tumors in mice treated with MSU-42011 exhibited reduced cell density and fewer actively proliferating cells compared to the control and bexarotene-treated tumors. Although bexarotene significantly (p < 0.01) elevated plasma triglycerides and cholesterol, treatment with MSU-42011 did not increase these biomarkers, demonstrating a more favorable toxicity profile in vivo. The combination of MSU-42011 and carboplatin and paclitaxel reduced macrophages in the lung and increased activation markers of CD8+T cells compared to the control groups. Our results validate our screening paradigm for in vitro testing of novel rexinoids and demonstrate the potential for MSU-42011 to be developed for the treatment of KRAS-driven lung cancer.